A novel prescription pedometer-assisted walking intervention and weight management for Chinese occupational population. - Yingxiang Yu; Yiran Lv; Bin Yao; Liguang Duan; Xiaoyuan Zhang; Lan Xie; Cuiqing Chang (PLoS ONE, 2018)
Information technology has been previously used for the research and practice of health promotion. Appropriate and effective health promotion methods used by professional groups remain to be investigated. This study aimed to assess the feasibility and effectiveness of a weight management program among the Chinese occupational population using and a novel information technology exercise prescription.A 3-month open, self-monitored intervention trial, involving individualized pedometer-assisted exercise prescription and a one-time targeted dietary guidance prior to exercise was conducted on the Chinese occupational population aged 18-65 years in China from 2015 to 2016. Data were collected from March 2015 to May 2016 and analyzed from June 2016 to August 2016. Participants were also asked to synchronize exercise data of the pedometer to the Internet-based Health System Center daily (at least weekly), by connecting to the personal computer (PC) using a USB cable or via Bluetooth.Eligible participants included 802 Chinese occupational persons, and 718 of them followed exercise interventions with 89.5% (718/802) adherence to the exercise programs. Of them, 688 participants completed the program with 85.8% (688/802) adherence to the exercise program and their data were analyzed. Weight decreased by 2.2% among all overweight/obese participants, with 1.8% reduction in waist circumference and 3.3% reduction in body fat percentage (p< 0.001). Weight and body fat percentage in normal-weight individuals decreased by 0.7% and 2.5%, respectively (p < 0.01). A weight gain of 1.0% was observed in all underweight participants (p< 0.05), and 68.2% (208/305) of overweight/obese participants experienced weight loss, with an average reduction of 3.5%, with 20.2% (42/208) of them achieving weight loss ≥5%. Blood pressure and fasting serum glucose decreased significantly in both the overweight/obese and the normal-weight individuals (p < 0.05). The incidence of hypertension was significantly lower and lifestyle behavior significantly improved (p < 0.05).The prescription pedometer-assisted walking intervention can effectively improve exercise adherence and manage weight. This approach was also effective in controlling the risk factors of weight-related chronic diseases.Chinese Clinical Trial Registry (ChiCTR) ChiCTR-OOh-16010229.